2010
DOI: 10.1111/j.1467-629x.2009.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Socially responsible investment fund performance: the impact of screening intensity

Abstract: Perhaps the most common criticism of socially responsible investment funds is that imposing non-financial screens restricts investment opportunities, reduces diversification efficiencies and thereby adversely impacts performance. In this study we investigate this proposition and test whether the "number" of screens employed has a linear or curvilinear relation with return. Moreover, we analyse the link between screening intensity and risk. Screening intensity has no effect on unadjusted (raw) returns or idiosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 41 publications
9
87
4
2
Order By: Relevance
“…Other studies point more attention on the systematic risk related to SRI fund performance. Lee, Humphrey, Benson and Ahn (2010) confirm that the number of screens negatively impacts performance, but also results in lower systematic risk. Humphrey and Lee (2012) provide a weak evidence that screening intensity increases (instead of decreases) risk-adjusted performance.…”
Section: Hypothesessupporting
confidence: 53%
“…Other studies point more attention on the systematic risk related to SRI fund performance. Lee, Humphrey, Benson and Ahn (2010) confirm that the number of screens negatively impacts performance, but also results in lower systematic risk. Humphrey and Lee (2012) provide a weak evidence that screening intensity increases (instead of decreases) risk-adjusted performance.…”
Section: Hypothesessupporting
confidence: 53%
“…A stream of the literature that overcomes this criticism comprises studies that analyse the performance of SRI mutual funds that apply exclusionary screens (Barnett and Salomon 2006;Renneboog et al 2008b;Lee et al 2010;Renneboog et al 2011;Humphrey and Lee 2011;CapelleBlancard and Monjon 2014;Humphrey and Tan 2014). In 10 In the Report from the Graver Committee it explicitly says that ''there is no consensus on one particular uniform ethical perspective''.…”
Section: Performance Effects Of Exclusionary Screeningmentioning
confidence: 99%
“…3 In contrast, Lee et al (2010) do not find any relationship (linear or curvilinear) between screening intensity and performance. Besides the US, Renneboog et al (2008) also include European and Asia-Pacific markets, having found that fund returns decrease with screening intensity on social and corporate governance criteria, but not on ethical, sin or environmental criteria.…”
Section: Introductionmentioning
confidence: 67%
“…Indeed, the typical approach in previous studies has involved comparing the performance of socially responsible funds as a whole relative to conventional funds, disregarding the fact that the former are not coherent in their social objectives and that not all dimensions of social responsibility are rewarded in the same way. Nevertheless, a few studies (Barnett and Salomon, 2006;Renneboog et al, 2008;and Lee et al, 2010) have tackled the type and intensity of social screens used as possible determinants of performance. Barnett and Salomon (2006) find a curvilinear relationship between the number of screens and risk-adjusted performance of US socially responsible funds.…”
Section: Introductionmentioning
confidence: 99%